DAMPAK DARI PENETAPAN UU NOMOR 26 TAHUN 2000 TERHADAP KEJAHATAN KEMANUSIAAN DAN GENOSIDA DI INDONESIA - ANWAR HAFIDZI (Syariah: Jurnal Hukum dan Pemikiran, 2015)
Until now several media in Indonesia is still preaching about violence in the name of religion, the burning of places of worship, Lapindo victims are still homeless, and many more events that involve the community in large numbers. Every human being has the right to live, but whether the appropriate law enforcement or still need improvement. This brief article will look at the impact of Law Number 26 on 2000 regarding Human Rights Court and its relevance to law enforcement. With the enactment of this Act, at least provides an opportunity to take back the cases of gross human rights violations that had occurred before the article appeared 43,44,46 of the Ad-hoc human rights court. Of course in the end, it is required for the support of law enforcement of?cials, political in?uence and a role of the community to criminalize of human rights although it is still the absence of explicit provisions in its implementation.